Immunomodulator clarithromycin enhances mucosal and systemic immune responses and reduces re-infection rate in pediatric patients with influenza treated with antiviral neuraminidase inhibitors: a retrospective analysis. - Wakako Shinahara (Public Library of Science (PLoS), 2013)
Background/aims Treatment with antiviral neuraminidase inhibitors suppresses influenza viral replication and antigen production, resulting in marked attenuation of mucosal immunity and mild suppression of systemic immunity in mice. This study investigated the effects of immunomodulator clarithromycin (CAM) supplementation on mucosal and systemic immunity in pediatric patients with influenza treated with neuraminidase inhibitors. Methods A retrospective, non-randomized case series study was conducted among five treatment groups of 195 children aged 5.9±3.3 years infected with influenza A in 2008/2009 season. The five treatment groups were oseltamivir (OSV), zanamivir (ZNV), OSV+CAM, ZNV+CAM and untreated groups. Anti-viral secretory IgA (S-IgA) levels in nasal washes and IgG levels in sera were measured. The re-infection rate was analyzed among the same five treatment groups in the 2009/2010 season. Results Treatment of influenza with OSV and ZNV for 5 days attenuated the induction of anti-viral S-IgA in nasal washes and anti-viral IgG in serum, compared with the untreated group. The combination of CAM plus OSV or ZNV boosted and restored the production of mucosal S-IgA and systemic IgG. The re-infection rates in the subsequent season were significantly higher in the OSV and ZNV groups than the untreated, while CAM+OSV and CAM+ZNV tended to reduce such rate. Conclusions CAM restored the attenuated anti-viral mucosal and systemic immunity and reduced the re-infection rate in the subsequent year in pediatric patients with influenza treated with OSV and ZNV.